CSI534 - Multimedia in Education February 1999 - PPSKOM, Pusat Pengajian Sains Komputer (1999)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 1998/99 February 1999 CSI534 • Multimedia in Education Duration : [3 hours] INSTRUCTION TO CANDIDATE: • Please ensure that this examination paper contains FIVE questions in FIVE printed pages before you start the examination. • Answer ALL questions. • You can choose to answer either in Bahasa Malaysia or English.